A new species of Pleurothallis (Orchidaceae: Pleurothallidinae) in subsection Macrophyllae-Fasciculatae with a unique, highly reduced, morphologically distinct labellum - Wilson, Mark (Universidad de Costa Rica, 2018)
Pleurothallis minutilabia, a species unique in subsection Macrophyllae-Fasciculatae because of the minute, highly reduced lip, is described and compared to the most similar species in the subsection. It is also compared morphologically to Pleurothallis kaynagata from section Abortivae, to which P. minutilabia is not related, but which also possesses a highly reduced lip. The morphology of the flower of P. minutilabia is discussed briefly in relation to possible pollination mechanisms. The distribution, restricted to Zamora Chinchipe, southern Ecuador, and the conservation status are addressed. Key words / Palabras clave: cloud forest, Ecuador, labellar morphology, Pleurothallis, pollination